Segment reporting and impairment of intangible assets in matrix organizations - Pitkälä, Jonna (fi=Turun yliopisto|en=University of Turku|, 2017)
The quality and accuracy of financial statements is of importance to the stakeholders of a company. The basis for the need to regulate financial statements stems from information asymmetry and the principal-agency problem that both cause inefficiencies to markets. The purpose of this thesis is to go through the IFRS 8 Operating segments and IAS 36 Impairment of assets from matrix organizations’ point of view. Both of these standards require identifying certain reportable units, namely operating segments and cash generating units. These reportable units should also be linked together. The organizational structure in matrix organizations possibly causes discrepancies between the operating segments and cash generating units because defining them in a multi-dimensional environment is not straightforward. Thus, the aim of this thesis is to explain how the two standards should be interpreted and applied in a matrix organization. Additionally, the aim is to clarify how the disclosures related to operating segments and impairment of intangible assets are presented in the financial statements of Finnish listed companies and further how they should be presented. The data has been collected in two phases. Firstly, the financial statements of 22 Finnish listed companies were analyzed in order to gain understanding on how the operating segments have been defined, what kind of intangible assets these companies hold in their balance sheets and further how the impairment testing for these intangible assets have been conducted and presented. Also the link between operating segments and cash generating units was under examination. Secondly, in order to deepen the different point of views, two auditors and two controllers performing the actual financial reporting and impairment testing were interviewed. The auditors represent the regulation side and their interest is to ensure accurate, open and correct disclosures. The companies’ interest is to balance between sensitive information and the requirements of IFRS. The results of this paper show that not understanding the link between IFRS 8 and IAS 36 is a common problem in matrix organizations. Segment reporting should represent the organizational structure and, further, the cash generating units and intangible assets should be aligned with the segments. Based on the sample of this thesis, validating that the financial statement has been prepared according to the standards is challenging, especially concerning the impairment testing.